PILATES EXERCISE EFFECTIVELY REDUCES MENSTRUAL PAIN IN ADOLESCENTS - Nursanti, Devy Putri Nursanti (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Dysmenorrhea, or menstrual pain, is a disruption in the flow of menstrual blood/pain during menstruation. If left untreated, dysmenorrhea can affect an individual's mental and physical function, necessitating non-pharmacological interventions. One such intervention is Pilates exercise. Pilates exercise can relax contracting muscles, stimulate the hypothalamus to produce endorphins as natural painkillers, resulting in a sense of comfort and reduced pain. This quasi-experimental study employed a non-equivalent control group design. The sample consisted of 15 adolescent girls selected through simple random sampling. Statistical analysis was conducted using the Wilcoxon test. The Wilcoxon test results showed a significant p-value of 0.001 < 0.05 (p < α). Pilates exercise leads to increased elasticity of abdominal muscles and elevated oxygen levels. Additionally, prostaglandin hormones are released during menstruation, resulting in reduced pain. The body also stimulates the hypothalamus to produce endorphins as natural painkillers, inducing a sense of comfort. Pilates exercise has an effect on reducing menstrual pain in adolescents in the Luksongo hamlet of Tugurejo village, Ngasem district, Kediri regency. Therefore, adolescents are advised to incorporate Pilates exercise to alleviate dysmenorrhea without causing side effects.